HUBUNGAN KINERJA KADER POSYANDU DENGAN KEPUASAN IBU BALITA DALAM PELAYANAN POSYANDU DI WILAYAH KERJA UPT PUSKESMAS SUKARAMAI KOTA MEDAN TAHUN 2024 - Simanullang, Elysa; Sinaga , Lia Rosa Veronika; Munthe, Seri Asnawati; Dachi, Rahmat Alyakin (Akupun Tour Publisher, 2024)
Background: The decrease in the number of visits by mothers of toddlers at the posyandu in the working area of ​​the UPT Puskesmas Sukaramai is something that needs to be paid attention to by health workers or cadres who work at the posyandu. Purpose: The aim of this research is to determine the relationship between the performance of posyandu cadres and the satisfaction of mothers of toddlers in posyandu services in the Sukaramai Community Health Center UPT Working Area, Medan City in 2024. Method: The population of this study was the number of mothers who made regular visits to the posyandu in the working area of ​​the UPT. Sukaramai Health Center, namely 507 toddlers. The number of samples was determined using the Slovin formula and the accidental sampling method as many as 84 people. Hypothesis testing used the Chi-square statistical test. The research results showed that the performance of posyandu cadres in the Sukaramai Health Center UPT Working Area, Medan City, was mostly (42.9%) in the poor category, 33.3% said the cadre performance was sufficient and only 23.8% said it was good. The majority of mothers (36.9%) felt dissatisfied with the satisfaction of mothers of toddlers who received services at posyandu in the working area of ​​the UPT Puskesmas Sukaramai Medan City, 35.7% felt quite satisfied, and only 27.4% felt satisfied with the performance of the cadres. in providing services. Disscusion and Conclusion: The results of the hypothesis test show that there is a relationship between the performance of Posyandu cadres and the satisfaction of mothers of toddlers in posyandu services in the working area of ​​the UPT Puskesmas Sukaramai with a value of p=0.003 (p<0.05). Seeing that there is a relationship between the performance of posyandu cadres and the satisfaction of mothers of toddlers with posyandu services in the work area of ​​the UPT. Puskesmas Sukaramai, it is necessary to make various efforts to improve the performance of posyandu cadres, such as training cadres to increase the satisfaction of mothers of toddlers with posyandu services. This will have an impact on increasing visits by mothers of toddlers to posyandu activities.